SOSIALISASI GERAKAN MELESTARIKAN BUDAYA LOKAL TERHADAP GENERASI Z DAN ALPHA DALAM MENJAGA BAHASA DAERAH DAN MAKANAN TRADISIONAL - Wahyuni, Nuorma; Canta, Dila Seltika; Setyaningsih, Erlin; Hermawansyah, Adi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The language ​​and traditional foods are an important part of Indonesia's identity and cultural heritage, reflecting the diversity and richness of the archipelago. However, the globalization and technological advances have led to a decline in interest in local culture among the younger generation. This community service activity aims to foster the interest, awareness, and active involvement of Generation Z and Generation Alpha in preserving regional languages ​​and foods through an educational, creative, and digital-based approach. The method is used the outreach and interactive discussion at the vocational high school in Balikpapan, involving participants in the creation of the digital content about regional languages ​​and foods. The results of the activity is demonstrating of increasing the insight and positive attitudes among participants in efforts to preserve and maintain local culture, particularly regional languages ​​and foods. The digital approach has proven effective in attracting the interest of the younger generation and making cultural preservation a form of self-expression that is relevant to current developments, while simultaneously strengthening patriotism and nationalism.